Exercise training during pregnancy reduces circulating insulin levels in overweight/obese women postpartum: secondary analysis of a randomised controlled trial (the ETIP trial) - Kirsti K. Garnæs; Siv Mørkved; Kjell Å. Salvesen; Øyvind Salvesen; Trine Moholdt (BMC, 2018)
Abstract Background The primary aim was to investigate if supervised exercise training during pregnancy could reduce postpartum weight retention (PPWR) three months after delivery in overweight and obese women. We also measured circulating markers of cardiometabolic health, body composition, blood pressure, and physical activity level. Methods This was a secondary analysis of a randomised controlled trial in which 91 women with BMI ≥ 28 kg/m2 were allocated 1:1 to an exercise program or a control group. Women in the exercise group were prescribed three weekly, supervised sessions of 35 min of moderate intensity walking/running followed by 25 min of resistance training. The control group received standard maternal care. Assessments were undertaken in early pregnancy, late pregnancy, and three months postpartum. PPWR was defined as postpartum body weight minus early pregnancy weight. Results Seventy women participated three months after delivery, and PPWR was −0.8 kg in the exercise group (n = 36) and −1.6 in the control group (n = 34) (95% CI, −1.83, 3.84, p = 0.54). Women in the exercise group had significantly lower circulating insulin concentration; 106.3 pmol/l compared to the control group; 141.4 pmol/l (95% CI, −62.78, −7.15, p = 0.01), and showed a tendency towards lower homeostatic measurement of insulin resistance (HOMA2-IR) (3.5 vs. 5.0, 95% CI, −2.89, 0.01, p = 0.05). No women in the exercise group compared to three women in the control group were diagnosed with type 2 diabetes postpartum (p = 0.19). Of the women in the exercise group, 46.4% reported of exercising regularly, compared to 25.0% in the control group (p = 0.16). Conclusions Offering supervised exercise training during pregnancy among overweight/obese women did not affect PPWR three months after delivery, but reduced circulating insulin levels. This was probably due to a higher proportion of women being active postpartum in the exercise group. Trial registration ClinicalTrials.gov ( NCT01243554 ), registration date: September 6, 2010.